Project Management Tools and Techniques : a Practical Guide - Carstens, Deborah Sater (CRC Press, 2013)
" ... step-by-step tools and techniques on the planning, execution and control of a project ... invaluable for the novice/student." Prof. William A Moylan, PhD, PMP, Eastern Michigan University, Farmington Hills, USA"; ... a very well written book. Simple, easy to follow, extremely practitioner and tool oriented and is very useful in real world from a novice user to most advanced user." Dr. Subramanyam Naidu Rayapati, IBM, Austin, Texas, USA.